The supermarket revolution in developing countries: Policies for "competitiveness with inclusiveness" - Reardon, Thomas; Gulati, Ashok (International Food Policy Research Institute, 2008)
A “supermarket revolution” has been underway in developing countries since the early 1990s. Supermarkets (here referring to all modern retail, which includes chain stores of various formats such as supermarkets, hypermarkets, and convenience and neighborhood stores) have now gone well beyond the initial upper- and middle-class clientele in many countries to reach the mass market. Within the food system, the effects of this trend touch not only traditional retailers, but also the wholesale, processing, and farm sectors. The supermarket revolution is a “two-edged sword.” On the one hand, it can lower food prices for consumers and create opportunities for farmers and processors to gain access to quality-differentiated food markets and raise incomes. On the other hand, it can create challenges for small retailers, farmers, and processors who are not equipped to meet the new competition and requirements from supermarkets. Developing-country governments can put in place a number of policies to help both traditional retailers and small farmers pursue “competitiveness with inclusiveness” in the era of the supermarket revolution. Some countries are already taking such steps, and their experiences offer lessons for others.